Dry-sliding wear of the 316L/h-BN composites produced under crack ammonia atmosphere - Chusong, Ekkarat; Kansuwan, Panya; Ohtake, Naoto; Wila, Pongsak; Tosangthum, Nattaya; Tongsri, Ruangdaj (My University, 2020)
Wear is one of different problems in mechanical failures of moving components. When a component encounters friction force on its surface, crack initiation tends to occur and wear follows crack propagation. Thus, the moving parts of automobiles should have proper wear resistance for long-time services, in addition to having high strength and hardness for heavy load operation. A self-lubricating material with compromised tribological and mechanical properties is important for some moving components. In this work, self-lubricating composites, metal matrix composites embedded with a solid lubricant, made from 316L stainless steel powder mixed with different hexagonal boron nitride (h-BN) contents of 10%, 15% and 20% by volume. The mixed powders were compacted into green parts (according with MPIF Standard 42) with density of 6.5 g·cm-3. Then, the green parts were sintered at 1100, 1150, 1200, 1250 and 1300°C under cracked ammonia (75% H2+25% N2) atmosphere for 60 min. The experimental results revealed that increases of hardness and strength sintered 316L matrix by reduction of pore amount and size were due to the increase of sintering temperature. However, the increase of h-BN content resulted in increase of pore amount and size. Additions of h-BN content up to 20 vol. % reduced friction coefficient of the sintered composites. At sintering temperatures of equal to and higher than 1200°C, h-BN did not react with 316L stainless steel powders to form intergranular boride phase. The sintered composites produced under the maximum experimental sintering temperature of 1300°C showed low specific wear rate.
Keywords: 316L stainless steel; Dry-sliding wear; Hardness; Hexagonal boron nitride; Self-lubricating composite